Event Related Potential Measurements of the Emotional Stroop Test in Athletes of Combat Sports - (:unkn) unknown (IEEE, 2014)
This research will investigate emotional processing of threat-relevant stimuli in athletes of combat sports by means of an ERP study. In this study, color-naming latency on threat-related words will be expected in athletes of combat sports on the Stroop task compared to athletes of non-combat sports; in other words, it is expected that there will be increased interference effect of threat-relevant stimuli on the Stroop task. In this context, participants will be shown neutral and threat-relevant stimuli randomly, and it will be investigated that whether the P300 wave of EEG show differences in response to threat-related words. After EEG data analysis, which were collected from four participants, it is found that ERP responses within the 280-400 ms time window, the amplitude of the total area of threat-related words is larger than neutral words for the group who are active in combat sports.